PENGARUH PENGGUNAAN VIDEO PEMBELAJARAN BERBAHASA INDONESIA TERHADAP KETERAMPILAN MENYIMAK SISWA KELAS IV SD - Sidebang, Restio; Ginting, Bijak; Rekhayana, Rajani (Unversitas Katolik Santo Thomas, 2025)
The objective of this study was to determine the effect of using Indonesian-language instructional videos on the listening skills of fourth-grade students at SD Negeri 030279 Sidikalang in the 2024/2025 academic year. This study employed a quasi-experimental method with a pretest-posttest control group design. The sample consisted of one class comprising 22 students. Data were collected using 10 multiple-choice questions, 5 short-answer questions, and observations. The results of data analysis showed a significant improvement in listening skills after using the Indonesian-language instructional videos, with the average pretest score of 33.40 increasing to a posttest score of 77.95. Statistical analysis using the paired sample t-test revealed a significant difference between the pretest and posttest scores, with a significance value (p-value) of 0.000 < 0.05. The calculated t-value was 7.240, which was greater than the t-table value of 2.012. Thus, the hypothesis testing results indicated that the alternative hypothesis (H1) was accepted and the null hypothesis (H) was rejected. These findings indicate that the use of Indonesian-language instructional videos has a positive effect on improving the listening skills of fourth-grade students at SD Negeri 030279 Sidikalang.